Mesenchymal Stem Cell-Derived Extracellular Vesicle Therapy for Stroke: Challenges and Progress - Bang, Oh Young; Kim, Eun Hee (Frontiers in Neurology, 2019)
ABSTRACT Stroke is the leading cause of physical disability among adults. Stem cells such as mesenchymal stem cells (MSCs) secrete a variety of bioactive substances, includ¬ing trophic factors and extra-cellular vesicles (EVs), into the injured brain, which may be associated with enhanced neurogenesis, angiogenesis, and neuroprotection. EVs are circular membrane fragments (30 nm–1 μm) that are shed from the cell surface and harbor proteins, microRNAs, etc. Since 2013 when it was first reported that intravenous application of MSC-derived EVs in a stroke rat model improved neurological outcomes and increased angiogenesis and neurogenesis, many preclinical studies have shown that stem cell-derived EVs can be used in stroke therapy, as an alternative approach to stem cell infusion. Although scientific research regarding MSC-derived EV therapeutics is still at an early stage, research is rapidly increasing and is demonstrating a promising approach for patients with severe stroke. MSC therapies have already been tested in preclinical studies and clinical trials, and EV-mediated therapy has unique advantages over cell therapies in stroke patients, in terms of biodistribution (overcoming the first pass effect and crossing the blood-brain-barrier), cell-free paradigm (avoidance of cell-related problems such as tumor formation and infarcts caused by vascular occlusion), whilst offering an off-the-shelf approach for acute ischemic stroke. Recently, advances have been made in the understanding of the function and biogenesis of EVs and EVs therapeutics for various diseases. This review presents the most recent advances in MSC-derived EV therapy for stroke, focusing on the application of this strategy for stroke patients.